Semiological nature of Kazakh, Kyrgyz and Karakalpak proverbs and sayings - Yeskeyeva, М.Қ.; Коssybayev, М.М. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2023)
A comprehensive research in the semantics of proverbs profoundly reveals the nature of a nation. The article contrasts semiotics of Kipchak languages group, particularly Kazakh, Kyrgyz and Karakalpak proverbs in the language system. The semantic scope of paremia is specified by the fact that the multi-level and multifunctional components of paremiosems in the internal structure of proverbs are formed by labeling and labeled signs. The article draws the line between the core and peripheral semantic components of proverbs, which is a complex linguistic sign. It also defines the features of a single paremiological meaning. Moreover, it identifies some labeling peculiarities of the explicit and implicit meaning in the content of proverbs. The relevance between sign and labeled concepts in the internal structure of paremias is studied in view of proverb user’s purpose and various cases. The research demonstrates that a single paremiological meaning is labeled within the semantic scope of tokens in the external structure of a proverb (substance and substance, substance and its attributes, etc.). The educational and rational value of proverbs are determined in terms of the entire system of social life and society as a whole. The authors explain the frequent occurrence of paremiological parallels in the Kazakh, Kyrgyz and Karakalpak languages, their identical labeling as a complex linguistic unit, the common life principles and customs of related nations in the context of the general Kipchak worldview.